Agelamadin F and tauroacidin E, bromopyrrole alkaloids from an Okinawan marine sponge Agelas sp. Issue 30 (22nd July 2015) - Kusama, Taishi; Tanaka, Naonobu; Kashiwada, Yoshiki; Kobayashi, Jun'ichi
Graphical abstract: Abstract: A new structurally unique bromopyrrole alkaloid, agelamadin F (1 ), comprising oroidin and 3-hydroxypyridinium was isolated from an Okinawan marine sponge Agelas sp. together with tauroacidin E (2 ), a new bromopyrrole alkaloid possessing a taurine moiety. Six known bromopyrrole alkaloids, oroidin, tauroacidin A, sceptrin, ageliferin, nagelamide E, and agelongine were also isolated and identified. The structures of 1 and 2 were elucidated on the basis of spectroscopic evidences, while chiral HPLC analysis suggested tauroacidin E (2 ) to be a racemate.